2012
DOI: 10.1074/jbc.m112.401364
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel LXXLL Motif in α-Actinin 4-spliced Isoform That Is Critical for Its Interaction with Estrogen Receptor α and Co-activators

Abstract: Background: ACTN4 potentiates nuclear receptor (NR)-mediated transcriptional activity. Results: The flanking sequences to the LXXLL motif in ACTN4 are important for both its association with ER␣ and co-activators. Conclusion: The ACTN4 (Iso) acts as a more potent co-activator of NRs than the corresponding ACTN4 (full length) through stronger interactions with known co-activators. Significance: This study describes a novel molecular mechanism by which ACTN4 (Iso) regulates transcription mediated by NRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…6D). This is consistent with our previous report that Gal-ACTN4 (Iso) has a higher transactivation activity than the wild-type protein, likely due to a better binding activity of ACTN4 (Iso) to p160 coactivators and the histone acetyltransferase activity PCAF than the ACTN4 (FL) (10).…”
Section: Actn4 Is a Transcriptional Coactivator Of Nf-bsupporting
confidence: 82%
See 2 more Smart Citations
“…6D). This is consistent with our previous report that Gal-ACTN4 (Iso) has a higher transactivation activity than the wild-type protein, likely due to a better binding activity of ACTN4 (Iso) to p160 coactivators and the histone acetyltransferase activity PCAF than the ACTN4 (FL) (10).…”
Section: Actn4 Is a Transcriptional Coactivator Of Nf-bsupporting
confidence: 82%
“…This finding was recently confirmed by An et al (8). We also established that ACTN4 has a regulatory function on transcription mediated by nuclear hormone receptors such as estrogen receptor, retinoic acid receptor, peroxisome proliferator-activated receptor, and vitamin D receptor via its N-terminal nuclear receptor-interacting motif, LXXLL (9,10). Notably, FSGS-linked ACTN4 mutants, which are predominantly cytoplasmic, lose their ability to potentiate hormone-dependent transcriptional activation (11).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…ACTN4 Potentiates and Interacts with GR␣ in a Ligand-dependent Manner-We have previously demonstrated that ACTN4 is a transcriptional coactivator for several transcription factors, including NRs (31). To test whether GR and ACTN4 interact in kidney cells, we carried out immunoprecipitation to examine whether endogenous GR and ACTN4 interact in HEK293T cells.…”
Section: Expression Of Gr␣ In Immortalized Hpcs and Primarymentioning
confidence: 99%
“…ii/ Modulation of gene transcription. It has been shown that α-actinin 4 interacts with nuclear receptors (estrogen receptor α in MCF-7 cells, vitamin D receptor in CV-1 cells, retinoic acid receptor and peroxisome proliferator-activated receptor γ in podocytes) and transcriptional co-activators (PCAF, SRC-1) through its LXXLL motif (Khurana et al, 2012a;Khurana et al, 2012b). Binding affinity to the nuclear factors was stronger in the alternatively spliced (short) isoform identified in a human cDNA library during earlier study (Chakraborty et al, 2006).…”
Section: Functionmentioning
confidence: 99%